Analysis of the Benefits of Product Recommendation Features in E-Commerce in Increasing Public Spending - Danny Ong; Imron Imron; M. Sinta Nurhayati; Andi Rosano (Journal of World Science, 2026)
Product recommendations generally appear when users search through search engines such as Google or directly on e-commerce platforms. The platform not only displays one option but also presents several alternatives from various sellers, allowing consumers the convenience of determining the best option according to their needs. Consumers generally expect a variety of product choices because they consider quality, price, and service simultaneously. Therefore, the presence of multiple recommendations is indispensable in today’s digital shopping ecosystem. Based on research conducted through surveys and supported by SWOT and Balanced Scorecard methods, it was concluded that the use of product recommendations in search received a high score, ranging from 4 to 5. These results suggest that product recommendations have the potential to increase public purchasing power; however, they may also encourage unplanned purchases by consumers. The problem previously faced was related to the lack of comprehensive product information on the platform. Platforms that are able to present the most complete and timely information tend to become the primary choice for consumers when shopping. This research identifies the function of product recommendations as a foundation for changing consumer mindsets while providing a wide variety of choices. With a neutral recommendation system, no seller can dominate the market unilaterally. This condition promotes fair pricing and encourages every seller to offer the best products to consumers.